Impact of migration on Helicobacter pylori seroprevalence in the offspring of Turkish immigrants in Germany - Porsch-Ozcürümez, Mustafa; Doppl, Wilhelm; Hardt, Philip Daniel; Schnell-Kretschmer, Henning; Tuncay, Mehmet; Akinci, Ahmet; Bilgin, Yaşar; Klör, Hans-Ulrich (The Turkish Journal of Pediatrics, 2003)
Helicobacter pylori (H. pylori) infection rates differ markedly between distinct populations. Consistent with previous findings of high seroprevalences in less developed countries, Turkish people have been reported to constitute a high-risk population. H. pylori prevalence rates have tended to be lower in Turkish individuals living in Germany for more than one generation. We conducted a seroepidemiological study to determine the impact of ethnicity, environmental setting, and sociodemographic factors on H. pylori seropositivity. Three subgroups were recruited encompassing 675 Germans (402 males, 273 females), 260 Turkish people born and raised in Germany (145 males, 115 females) and 148 Turkish people living in Turkey (91 males, 57 females), Ages ranged from newborn to a maximum of 30 years in all subgroups. H. pylori immunoglobulin G serum antibodies were determined by a commercial ELISA. H. pylori age-adjusted overall seroprevalence clearly differed between Germans (13.1%) and Turkish subgroups, with prevalences of 30.4% (Turks in Germany) and 44.5% (Turks in Turkey) seropositive individuals (p